1994
DOI: 10.1111/j.1600-0447.1994.tb05787.x
|View full text |Cite
|
Sign up to set email alerts
|

Mania

Abstract: 3258 randomly selected houshold residents of Edmonton, Alberta were interviewed by trained lay interviewers using the Diagnostic Interview Schedule (DIS). The lifetime prevalence of mania was 0.6%, for both sexes combined. Lifetime morbidity risk was 1.4% for men and 0.6% for women. The mean age of onset was 20 years of age for both men and women. Ninety-five percent of bipolar individuals had had their first onset by age 26, and less than 5% had their onset before the age of 10. The mean number of manic episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 44 publications
2
11
0
1
Order By: Relevance
“…The median numbers of manic (14) and depressive (6) episodes found here are also similar to those in treatment samples (Clayton, 1981). The finding that 20 % of cases never had a depressive episode is within the range of 5 to 28 % reported in clinical studies (Abrams et al 1979 ;Andreasen et al 1988 ;Wolf et al 1988 ;Fogarty et al 1994). However, the finding that this proportion is much greater for men (38n9 %) than women (4n1 %) is a new result requiring replication.…”
Section: Coursesupporting
confidence: 78%
“…The median numbers of manic (14) and depressive (6) episodes found here are also similar to those in treatment samples (Clayton, 1981). The finding that 20 % of cases never had a depressive episode is within the range of 5 to 28 % reported in clinical studies (Abrams et al 1979 ;Andreasen et al 1988 ;Wolf et al 1988 ;Fogarty et al 1994). However, the finding that this proportion is much greater for men (38n9 %) than women (4n1 %) is a new result requiring replication.…”
Section: Coursesupporting
confidence: 78%
“…Four studies examined the comorbidity of eating disorders and BD in community populations (15, 17–19). These studies differed in their inclusion of syndromal versus spectrum bipolar and eating disorders and subject demographics.…”
Section: Resultsmentioning
confidence: 99%
“…In the first survey, Fogarty et al. (17) examined 3,258 residents of Edmonton, Canada aged 18 years and older using the Diagnostic Interview Schedule (DIS). In their analysis, which did not include subthreshold cases, there was no significant evidence of comorbidity between BD and anorexia nervosa.…”
Section: Resultsmentioning
confidence: 99%
“…Convergent evidence from large-scale populationbased studies has demonstrated a greater association of alcohol dependence [7,12,19,28] with bipolar disorder than with major depressive disorder. Moreover, the NCS study reported that alcohol dependence-mania comorbidity was greater in males than in females (e.g., OR = 12.0 for males, OR = 5.0 for females) [19].…”
Section: Introductionmentioning
confidence: 99%